Electromagnetic navigation system for acetabular component placement in total hip arthroplasty is more precise and accurate than the freehand technique: a randomized, controlled trial with 84 patients - Mihalič, Rene; Zdovc, Jurij; Mohar, Janez; Trebše, Rihard (Acta Orthopaedica, 2020)
Background and purpose — The accuracy of conventional navigation systems depends on precise registration of bony landmarks. We investigated the clinical use of electromagnetic navigation (EMN), with a unique device for precise determination of the anterior pelvic plane. Patients and methods — We randomly allocated patients scheduled for total hip arthroplasty into 2 groups of 42 patients each. In the study group, cups were placed at the predetermined target angles (inclination: 42.5°; anteversion: 15°) with the support of EMN. In the control group, cups were placed freehand aiming at the same target angles. Postoperatively the true position of the cup was determined using computed tomography scan of the pelvis. Precision (root mean squared error, RMSE) bias (mean bias error, ME), accuracy, and duration of surgery were compared between the methods. Results — Cup anteversion was more accurate and precise in the navigated group. The ME in the navigated and freehand group was –1.7° (95% CI –2.4 to 1.1) and –4.5° (CI –6.5 to 2.5), respectively. The RMSE in the navigated and freehand group was 2.8° (CI 2.3–3.2) and 8.0° (CI 6.3– 9.5), respectively. The inclination was also more precise in the navigated group, with the RMSE in the navigated and freehand group at 4.6° (CI 3.4–5.9) and 6.5° (CI 5.4–7.5), respectively. The accuracy of the inclination and the duration of surgeries were similar between the groups. Interpretation — Cup placement with the help of EMN is more precise than the freehand technique and it does not affect the duration of surgery.